The nature and drivers of food innovation in UK-based SMEs - Chen, Tianqi (2015)
Innovation has been increasingly important in the development of one company. Nowadays, in the competitive market, both large firms and small enterprises pay much attention to innovation. As innovation is an efficient way to create corporate differentiate and increase competitive force for companies. Specifically in the food sector innovation is at the core of organizational growth. Yet there are few studies examining the nature of innovation in the food sector in the UK. There are different types of innovation be adopted on the base of varied resources companies have. As a result that both incremental and radical innovation, product or process innovation have their typical characteristics together with distinctive requirements of sources. The research investigates the nature of innovation in the food sector in the UK. More specifically it examines product innovation within UK SMEs in the food sector and the drivers for product innovation. There are two perspective of understanding innovation activities. In terms of internal factors, product innovation in a firm is highly linked with R&D intensity, while in an external perspective, consumers’ demand and market changes determine product improvement to a large extent. However, the traditionally ‘market-pull’ or ‘technology-push’ is limited to explain innovation comprehensively. For the level of innovation in a firm, it is not as simple as only linked with R&D and market, but closely related with the dominant orientation, size, and suppliers and positioning of the firm. What’s more, innovation activities are highly dependent on the source of knowledge and information, cooperation and governance structure in a company. Therefore, companies, especially SMEs, should take careful decision on innovation adoption in different situation according to both internal and external factors.